Rút gọn biểu thức sau

Question

Rút gọn biểu thức sau
rut-gon-bieu-thuc-sau

in progress 0
Ben Gia 1 year 2020-11-29T06:11:27+00:00 2 Answers 37 views 0

Answers ( )

    0
    2020-11-29T06:12:41+00:00

    `(x^2-5x+1)^2+2(5x-1)(x^2-5x+1)+(5x-1)^2`

    `=x^4-10x^3+27x^2-10x+1+2(5x^3-x^2-25x^2+5x+5x-1)+25x^2-10x+1`

    `=x^4-10x^3+42x^2-20x-2+2(5x^3-26x^2+10x-1)`

    `=x^4-10x^3+42x^2-20x+2+10x^3-52x^2+20x-2`

    `=x^4`

     

    0
    2020-11-29T06:12:46+00:00

    Đáp án:

    ${x^4}$

    Giải thích các bước giải:

    $\begin{array}{l}
    {\left( {{x^2} – 5x + 1} \right)^2} + 2\left( {5x – 1} \right)\left( {{x^2} – 5x + 1} \right) + {\left( {5x – 1} \right)^2}\\
     = {\left( {{x^2} – 5x + 1 + 5x – 1} \right)^2}\\
     = {\left( {{x^2}} \right)^2}\\
     = {x^4}
    \end{array}$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )